English Aksesibilitas Pariwisata Berdasarkan Pengalaman Penyandang Tunanetra di Kota dan Kabupaten Bandung: Artikel jurnal ini berisi tentang kondisi aksesibilitas pariwisata berdasarkan perspektif penyandang tunanetra - Apriliani, Resya; Priyanto, Rahmat (JURNAL KEPARIWISATAAN, 2025)
This research aims to examine how the condition of tourism accessibility is based on the experience of People with visual impairment in Bandung City and Regency. This research employs a descriptive qualitative research design, utilizing in-depth interviews, to explore the experiences of five individuals with visual impairments during tourism activities and the obstacles they encounter. The results showed that physical aspects, such as special infrastructure, are not yet accessible, and their availability is not yet evenly distributed in every type of tourist destination. In addition, transportation and accommodation are not fully accessible for people with visual impairments. The lack of specialized infrastructure is the reason for the sector's inaccessibility. The next aspect that is already reasonably accessible is access to information; the availability of digital information can make it easier for visually impaired people to access information about tourist trips. However, visually impaired people are still constrained by social access, where many people with visual impairment still experience discrimination from staff and local communities. The solution to this problem is to increase the development of special infrastructure and provide training and education about the needs of visually impaired people. This will enable local community fund staff to create inclusive tourism.